Can artificial intelligence and space technology transform livestock insurance and rangeland management? - Onyango, Polycarp Otieno; Paliwal, Ambica (International Livestock Research Institute, 2024)
A new study shows that artificial intelligence (AI) could improve the accuracy of index-based livestock insurance (IBLI) satellite assessments in regions affected by invasive plant species.